Forecasting The Indicators Of Foreign Trade In Syria Dr. Maain Dyoub * Moder Yousef ** - ديوب معن; يوسف مضر (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this study was to apply Box- Jenkins methodology represented by ARIMA models, to forecast some indicators of foreign trade in Syria, and to know if these models are effective in forecasting. The main results were: -The time series for the indicator of trade exposure in Syria for period 1992 - 2016 is unstable, and then stabilized after making the first differences.-The time series for the indicator of import- export covering in Syria for period 1992 - 2016 is unstable, and then stabilized after making the first differences. - ARIMA (1,1,1) model, which is the suitable model to forecast the indicator of trade exposure, and it is effective model. - ARIMA (2,1,0) model, which is the suitable model to forecast the indicator of import- export covering, and it is effective model.